IPPIS Policy and the Challenges of its Implementation in the Nigerian Universities: A Conceptual Discourse - Bello, Matthew Funsho; Mela, Keneth (NIU Journal of Social Sciences; Vol 8 No 3 (2022): NIU Journal of Social Sciences, Vol. 8 No. 3, September 2022, 2022)
The Integrated Personnel and Payroll Information System (IPPIS) programme was introduced by the Nigeria Federal Government supported by the World Bank as one of the measures of Public Service Reform. Prior to the introduction of this scheme, Ministries, Departments and Agencies (MDAs) received their recurrent costs on monthly basis as subvention. The above arrangement gave room for the MDAâ€™s to disburse money sent to them whenever and however they deemed fit. This therefore according to records led to financial misconduct in the Nigerian Civil Service. The huge amount spent on recurrent expenditure, if not monitored and cut down through appropriate government policy, could lead to cases of corruption the civil service. Hence, the need for Nigerian Government to provide accurate and correct number of civil servants under her care and to an extent minimize budget estimate via IPPIS programme. This research work examined the benefits and problems of incorporating the university system into IPPIS programme by Federal government of Nigeria. The paper undertakes a theoretical grinding of critical issues under study by adopting a review of periodic publications, journals and related secondary materials. The research used qualitative method in the study. The study revealed that, university system does not reject IPPIS but argued that IPPIS do not adequately capture its flexibility and peculiarities. So, there is the need to take into consideration its demand in the IPPIS software application via UTAS software. The study also discovered many shortfalls and benefits of incorporating university system in to IPPIS programme by the federal government. The study therefore recommends that the implementation of IPPIS policy by federal government should adequately capture the flexibility and peculiarities of the University System; and that, both parties (Federal government and University community) should consider likely consequences of their misunderstanding which might negatively affect the general public. Keywords :  IPPIS Policy, UTAS Software, Federal University Gashua-Nigeria, Government, Employees